Comparing Co‐catalytic Effects of ZrOx, SmOx, and Pt on COx Methanation over Co‐based Catalysts Prepared by Double Flame Spray Pyrolysis. Issue 12 (5th May 2021) - Stahl, Jakob; Ilsemann, Jan; Pokhrel, Suman; Schowalter, Marco; Tessarek, Christian; Rosenauer, Andreas; Eickhoff, Martin; Bäumer, Marcus; Mädler, Lutz
Abstract: The impact of different co‐catalytically acting promoters (Pt, ZrOx and SmOx ) during COx methanation was investigated on alumina supported Co‐based model catalysts. To obtain samples with identical structure and morphology independent of the presence and the type of promoter added, double flame spray pyrolysis was employed for the synthesis, which, in contrast to classical catalyst preparation techniques, allows controlling and separating the particle formation processes of the different catalyst components. In this way, differently promoted and unpromoted catalysts with identical size distributions and dispersions could be synthesized to study co‐catalytic effects in isolation. For CO2 methanation, all promoters led to improved methanation yields and long‐term activities within the whole temperature range as compared to the unpromoted catalyst. Among them, zirconia and platinum performed best. In case of CO methanation, a beneficial influence of the studied promoters could also be verified – with Pt showing the best results. Yet, all catalysts deactivated rapidly above 310 °C, limiting their usability to lower temperatures. Abstract : Team up : The catalytic hydrogenation of COx is a process of key importance for the chemical storage of renewable energy. For this application, promoter effects of ZrOx, SmOx and Pt, added to 20 wt.% Co‐Al2 O3 catalysts, were compared. The potential of double flame spray pyrolysis to synthesize highly defined model catalysts with identical morphology – independent of the presence and the type of promoter added – was demonstrated. This way promotor effects could be studied in isolation.